EXPLORATION OF ECONOMICALLY IMPORTANT FODDER PLANTS OF DISTRICT RAJOURI - JAMMU AND KASHMIR STATE: Life Science-Ethnobotany - DR. ABDUL RASHID; SHARMA, ANIL (International Journal of Life Science and Pharma Research, 2012)
An ethnobotanical analysis was conducted in order to document the traditionally used fodder plants in the study area. The present investigation is based on the extensive survey and collection of plants from district Rajour of Jammu and Kashmir State in India, from September 2010 to June February 2012. A total of sixty eight plant species belonging to forty two families were reported form the study area. Agriculture along with animal husbandry is still the principal occupation and source of livelihood for over 80% of the population of study area. District Rajouri is well endowed with variety of livestock. Large population and low productivity are the hallmark of livestock in the region. The diversity of fodder plants is a proportion of the enormous biodiversity occurring in this part of the North Western Himalaya. A panorama of the biodiversity emerged in this study, which is of both intangible value and direct value for the livestock-and mountain communities living in the region. The findings suggest a very high scope of the utilisation of this natural and uncultivated biodiversity for supporting livestock-based livelihoods in the region.